The impact of diabetes on young transplant recipients: An American perspective. Issue 5 (18th January 2022) - Loera, Jackquelin M.; Barrett, Spencer C.; Zhang, Theodore S.; Anand, Adrish; Awan, Ahmed A. Y.; Murthy, Bhamidipati V. R.; O'Mahony, Christine A.; Goss, John A.; Rana, Abbas A.
Abstract: Despite advancements in diabetic care, diabetic kidney transplant recipients have significantly worse outcomes than non‐diabetics. Aim: Our study aims to demonstrate the impact of diabetes, types I and II, on American young adults (18–40 years old) requiring kidney transplantation. Methods: Using the United Network for Organ Sharing database, we conducted a population cohort study that included all first‐time, kidney‐only transplant recipients during 2002–2019, ages 18–40 years old. Patients were grouped according to indication for transplant. Primary outcomes were cumulative all‐cause mortality and death‐censored graft failure. Death‐censored graft failure and patient survival at 1, 5, and 10 years were calculated via the Kaplan–Meier method. Multivariate Cox regression was used to assess for potential confounders. Results: Of 42 466 transplant recipients, 3418 (8.1%) had end‐stage kidney disease associated with diabetes. At each time‐point, cumulative mortality was higher in diabetics compared to patients with non‐diabetic causes of renal failure. Conversely, cumulative graft failure was similar between the groups. Adjusted hazard ratios for all‐cause mortality and graft failure in diabetics were 2.99 (95% CI 2.67–3.35; p  < .01) and 0.98 (95% CI 0.92–1.05, p  < .01), respectively. Conclusion: Diabetes mellitus in young adult kidney transplant recipients is associated with a nearly three‐fold increase in mortality, reflecting a relatively vulnerable patient population. Identifying the underlying causes of poor outcomes in this population should be a priority for future study. SUMMARY AT A GLANCE: Using UNOS data, this work strengthens existing evidence regarding poorer outcomes in the diabetic transplant population, in particular those in the younger age group of 18–40 years of age. There are increased mortality rates amongst diabetic kidney transplant recipients compared to the non‐diabetic cohort, though there was no difference in death‐censored graft survival.